Syntactical differences and language usage的确and 实在in chinese - Toktarbek, S. (Journal of Oriental Studies, 2016)
The article examines the syntactic differences and language usage 的确and 实在in Chinese. At the same time the author is given a training technique sinonomichnyh series of Chinese language.